2002
DOI: 10.1093/ajcn/75.5.887
|View full text |Cite
|
Sign up to set email alerts
|

Dietary silicon intake and absorption

Abstract: Solid foods are a major source of available silicon. The association between dietary silicon intake and bone health should now be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
235
1
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(256 citation statements)
references
References 24 publications
10
235
1
10
Order By: Relevance
“…The intake from the British diet has been estimated to be 20-50 mg silicon/day (Bellia et al, 1994;Bowen et al, 1984, Pennington, 1991, corresponding to 0.3-0.8 mg/silicon/kg bw/day for a 60 kg person. These data are in the same range as mean estimated silicon intakes in the USA (30 and 33 mg silicon/day in men, and 24 and 25 mg silicon/day in women in two cohorts, respectively) (Jugdaohsingh et al, 2002).…”
Section: Siliconsupporting
confidence: 64%
See 1 more Smart Citation
“…The intake from the British diet has been estimated to be 20-50 mg silicon/day (Bellia et al, 1994;Bowen et al, 1984, Pennington, 1991, corresponding to 0.3-0.8 mg/silicon/kg bw/day for a 60 kg person. These data are in the same range as mean estimated silicon intakes in the USA (30 and 33 mg silicon/day in men, and 24 and 25 mg silicon/day in women in two cohorts, respectively) (Jugdaohsingh et al, 2002).…”
Section: Siliconsupporting
confidence: 64%
“…Berlyne et al (1986) found slightly higher urinary silicon excretion in 23 normal individuals (about 33 mg of silicon/day). Jugdaohsingh et al (2002) reported urinary excretion of silicon around 20 mg/day in young adults.…”
Section: General Information On the Metabolic Fate Of Siliconmentioning
confidence: 99%
“…In general terms, there appear to be two distinct steps involved in biodistribution of dietary silicon after oral absorption: first, the rapid urinary excretion for most of the ingested silicon [9,15,25]; the other step would consist of tissue storage and/or metabolism for the minor part of the ingested Si, proportional to physiological balance [25]. In a human study using Si radioactive, Popplewell et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…Si occurs naturally mainly as silicon dioxide (SiO 2 ) or as silicic acids derived from the hydration of this oxide, while orthosilicic acid [Si(OH) 4 ] is the simplest and the major chemical form of water soluble Si (and it is found mainly in beverages) [13]. In addition, the presence of the orthosilicic acid is known as the biological form of silicon in humans and animals and plays a major role in the release of silicon into living cells [2,4,[14][15][16]. Despite the fact that Si is mainly absorbed from our diet as orthosilicic acid, when present in higher concentrations (it is stable only in concentrations lower than 10 −4 M ∼ = 10 mg/L) and with no addition of stabilizers to prevent self-association, this form of silicon polymerizes and forms silica (SiO 2 ) which allows very limited bioavailability (absorption ranging from 1% to 20%) [17].…”
Section: Introductionmentioning
confidence: 99%
“…OSA is accepted as being the natural biological form of silicon (Si) in humans and animals and plays a major role in delivering silicon to the living cells (Reffitt et al, 1999;Jugdaohsingh et al, 2000;Jugdaohsingh et al, 2002;Sripanyakorn et al, 2009;Jurkić et al, 2013). The availability of silicon from a given source depends on the solubility or speciation of the compound concerned (Van Dyck et al, 1999).…”
Section: Introductionmentioning
confidence: 99%